2014
DOI: 10.1038/emm.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

miR-27 regulates mitochondrial networks by directly targeting the mitochondrial fission factor

Abstract: Mitochondrial morphology is dynamically regulated by forming small, fragmented units or interconnected networks, and this is a pivotal process that is used to maintain mitochondrial homeostasis. Although dysregulation of mitochondrial dynamics is related to the pathogenesis of several human diseases, its molecular mechanism is not fully elucidated. In this study, we demonstrate the potential role of miR-27 in the regulation of mitochondrial dynamics. Mitochondrial fission factor (MFF) mRNA is a direct target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 61 publications
0
25
1
Order By: Relevance
“…Molecular study found that miR‐761 binds with 3′‐UTR of MFF mRNA for its downregulation . MiR‐27 also targets 3′‐UTR of MFF mRNA to suppress its expression and this inhibition favours enhanced mitochondrial elongation and fusion . Another member of miRNA family, miR‐484, attenuate Fis1‐induced mitochondrial fission and apoptosis in cardiomyocytes by binding with the amino acid coding region of Fis‐1 and inhibition of its translation.…”
Section: Mirnas Modulate Mitochondrial Fission and Fusion Proteinsmentioning
confidence: 99%
“…Molecular study found that miR‐761 binds with 3′‐UTR of MFF mRNA for its downregulation . MiR‐27 also targets 3′‐UTR of MFF mRNA to suppress its expression and this inhibition favours enhanced mitochondrial elongation and fusion . Another member of miRNA family, miR‐484, attenuate Fis1‐induced mitochondrial fission and apoptosis in cardiomyocytes by binding with the amino acid coding region of Fis‐1 and inhibition of its translation.…”
Section: Mirnas Modulate Mitochondrial Fission and Fusion Proteinsmentioning
confidence: 99%
“…Furthermore, mitochondrial fission and the regulator of mitochondrial fission Drp1 are influenced by increased metabolic demands and apoptotic stress (Cereghetti et al, 2010;Rambold et al, 2011). Recently, it has come to light that the regulation of mitochondrial dynamics is also governed by miRNAs (Wang et al, 2011a;Tak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For reporter analysis, Enhanced green fluorescent protein (EGFP) reporter vectors were constructed by inserting 3′UTR region of MFF mRNA (1509–1778 bp) into pEGFP-C1 (BD Bioscience) (41). A mutant reporter lacking the binding sites for the miR-200a-3p seed region was generated by site-directed mutagenesis using a KOD-Plus-Mutagenesis Kit (Toyobo).…”
Section: Methodsmentioning
confidence: 99%